Synthesis of highly active biocompatible ZrO2 nanorods using a bioextract. Issue 16 (November 2020) - Isacfranklin, M.; Dawoud, Turki; Ameen, Fuad; Ravi, G.; Yuvakkumar, R.; Kumar, P.; Hong, S.I.; Velauthapillai, Dhayalan; Saravanakumar, B.
Abstract: The use of organic–inorganic metal oxide products in biomedical applications has emerged as the most expanding field. To have long-lasting stability and improved reliability, a biomaterial must be specially chosen and have bioactivity and mechanical properties from the application's point of view. Rambutan ( Nephelium lappaceum L.) fruit is considered as one of the bioactive components. In this study, ZrO2 is prepared by hydrothermal route using a green rambutan extract as a reducing agent and it used for biomedical applications. It was found that ZrO2 nanorods hamper the growth of cancerous cells in a dose-dependent manner at a half-maximum inhibitory concentration of 55.32 μg mL −1 . Phase-contrast microscopic studies confirm that ZrO2 nanorods disrupt the cell membrane and induce cell death. Keeping this in mind, ZrO2 nanorods can be a promising agent in biomedical applications.